Enhanced Antimalarial Efficacy of Annona muricata Leaf Extract Combined With Artesunate, Chloroquine, and Pyrimethamine in Plasmodium berghei–Infected ICR Mice - Orawan Sarakul; Rachasak Boonhok; Voravuth Somsak (Advances in Pharmacological and Pharmaceutical Sciences)
Malaria continues to be a significant global health challenge, particularly in tropical and subtropical regions, due to its high morbidity and mortality rates. The development of resistance to conventional antimalarial drugs underscores the urgent need for novel therapeutic approaches. Artemisinin-based combination therapies (ACTs) are effective but face emerging resistance issues. This study explores the antimalarial efficacy of Annona muricata leaf extract (AME) when combined with artesunate (ART), chloroquine (CQ), and pyrimethamine (PYR) in Plasmodium berghei–infected ICR mice. Fresh A. muricata leaves were processed to produce a crude ethanolic extract. ART, CQ, and PYR were prepared and administered to ICR mice infected with P. berghei ANKA. The study evaluated the parasitemia levels and survival rates, comparing combination treatments to monotherapies. The combination treatments were analyzed for synergistic interactions. Results indicated that AME alone exhibited significant antimalarial activity, especially at higher doses. The combination of AME with ART and PYR demonstrated significant synergistic effects, achieving over 90% inhibition of parasitemia and significantly prolonging mean survival times up to 30 days. However, the combination of AME with CQ did not show synergistic effects. These findings suggest that AME, particularly in combination with ART or PYR, could enhance antimalarial efficacy and offer a promising alternative to current treatments, potentially mitigating drug resistance issues. Further research is warranted to validate these combinations and explore their mechanisms of action.